The Evidentiary Value of a Bill of Lading in Algerian Law - Bokada, Abdelkrim (Journal of Legal Studies and Researches, 2017)
The maritime bill of lading is of great importance, especially after the developments it has undergone, as it has transformed from a message into a document that represents the goods transported by sea and takes the place of possession of the goods themselves. Consequently, it has come to play an important role in commercial exchanges, and thus it has acquired evidentiary power through the data included in it, which has made it a tool that proves and represents the goods between its parties.